Prejudice against foreign students in university : does priming articles reduce implicit prejudice? - Sor, Hong Yuen. (2013)
Study 1 of the present research investigates whether Singaporean students display a greater degree of prejudice against foreign students from China, compared to foreign students from other nationalities. It also aims to find out whether psychological and social factors, such as perceptions of realistic threats, symbolic threats and the need of dependence as well as the social interactions contribute to the prejudice. Study 2 addresses how Regulatory Focus Theory used in the framing of prevention or promotion-focused priming messages reduces implicit prejudice against students from China. The findings revealed that a) Singaporean students expressed more hostility against students from China compared to the other foreign students. b) The prejudice was sufficiently attributed to the presence of realistic threats alone, specifically financial threats. c) The understanding of the need of Singapore’s dependence on foreign talents did not mediate the prejudice. d) In-depth social interactions alleviate the prejudice against students from China and it was the most predictive factor for prejudice among factors related to prejudice. e) Regardless of the framing of the focus, priming articles did not reduce implicit prejudice against students from China. f) Individuals who had high perceptions of realistic threats displayed a greater degree of hostility towards students from China after reading the articles. Therefore, policymakers should first aim to address the notion that students from China pose a threat to the current Singaporean way of life in order to minimize prejudice. It could be done through promoting in-depth social interactions. Publishing articles defensive of the decision to award scholarships to China-born students may backfire.